Visual Outcomes and Local Control After Fractionated Stereotactic Radiotherapy for Optic Nerve Sheath Meningioma. Issue 3 (May 2018) - Hamilton, Sarah Nicole; Nichol, Alan; Truong, Pauline; McKenzie, Michael; Hsu, Fred; Cheung, Arthur; Dolman, Peter; Gete, Ermias; Ma, Roy
Abstract : Purpose: To review the outcomes of patients with optic nerve sheath meningiomas (ONSM) treated with fractionated stereotactic radiotherapy. Methods: Patient characteristics, treatment, and outcomes were analyzed for all patients with primary and secondary ONSM treated from 2001 to 2012. Clinically significant visual acuity change was defined as a 2-line change on the Snellen eye chart from pre-fractionated stereotactic radiotherapy. Results: Forty-one patients were treated: 23 patients with primary ONSM and 18 patients with secondary ONSM. The median age at diagnosis was 56 years. The median visual follow up was 3.8 years and the median radiologic follow up was 4.4 years. At diagnosis, 36% had normal vision (20/20–20/40), 10% had mild impairment (<20/40–20/60), 20% had moderate visual impairment (<20/60–20/200), 27% had severe impairment (<20/200), and 7% had no light perception. Common acute side effects were headache (32%) and nausea (15%); 15% of patients required corticosteroids during stereotactic radiotherapy. Chronic toxicities included retinopathy (7%), pituitary dysfunction (13%), chronic ocular pain (5%), and cataracts (2%). Visual acuity was stable in 65%, improved in 27%, and decreased in 8% of patients. Visual fields were stable in 70%, improved in 21%, and reduced in 9%. Actuarial 5-year local control rates were 100% for primary ONSM and 88% for secondary ONSM. Actuarial 5-year visual preservation rates were 100% for primary ONSM and 86% for secondary ONSM. Conclusions: Fractionated stereotactic radiotherapy for primary and secondary ONSM was well tolerated and provides excellent local control and visual preservation. Longer follow up is required to determine the risk of late ocular and pituitary sequelae. Abstract : Radiotherapy for optic nerve sheath meningioma results in excellent local control and visual preservation.